2019
DOI: 10.15516/cje.v21i0.3449
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Journalism Education - the Only Possible Way to the Future / Održivo obrazovanje novinara – jedini mogući put u budućnost

Abstract: There have been only a few attempts so far of setting journalism education in the context of sustainability, but there is not the theoretical proposition of the general paradigm of sustainable journalistic education. By critical analysis of the tradition of journalism education and research of it, the paper identifies all emergences of journalistic education in the context of development and sustainability. Based on the evolution of academic proposals to advance journalism education, most current references ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…They should have a deeper understanding of the issues in charge, deal with them, and respond appropriately to such challenges. Sustainable journalism studies could meet these needs by focusing on journalistic academics and applying a holistic educational perspective (Vukić, 2019).…”
Section: Kbjcmentioning
confidence: 99%
“…They should have a deeper understanding of the issues in charge, deal with them, and respond appropriately to such challenges. Sustainable journalism studies could meet these needs by focusing on journalistic academics and applying a holistic educational perspective (Vukić, 2019).…”
Section: Kbjcmentioning
confidence: 99%
“…However, it must be concluded that no wider picture was presented; respectively there is a lack of concrete proposal for restructuring the journalism higher education system regarding the information disorder phenomenon. Therefore, the sustainable journalism education paradigm (Vukić, 2019) could answer the above challenges because its key mechanisms are self-renewal and self-regulation, as introducing new content in the curriculum is not enough for deeper and systemic changes. Nevertheless, such sources are the most numerous since they are the most convenient -surface interventions are cheap, fast and mostly depend on the teacher.…”
Section: Academic Journalism Education As a Preventionmentioning
confidence: 99%
“…To nadalje podrazumijeva i samostalno i participativno učenje činjenjem koje je dio suvremene visokoškolske nastavne prakse, 7 a čiji korijeni sežu do teorije progresivnoga učenja popularnog u SAD-u 20. stoljeća i Johna Deweya. Na kraju, ali ne i manje važno, s obzirom na to da se u studiji ovoga slučaja naglašava cjelovito obrazovanje studenata, može se osloniti i na holističku teoriju obrazovanja, posebno u kontekstu novinarstva (Vukić, 2019).…”
Section: Radio Kao Obrazovni Masovni Medij Nastavno Sredstvo I Metodunclassified
“…Razumijevajući studentske radijske aktivnosti kao one najvišeg stupnja medijske edukacije, riječ je o obrazovanju novinara što je tradicionalno predmet proučavanja više grana komunikacijskih znanosti (komunikologije, masovnih medija i novinarstva), a neki je znanstvenici vide i kao samostalnu istraživačku disciplinu (npr. Deuze, 2006;Vukić, 2019). Naime, postoji argumentirani stav pojedinih autora (npr.…”
Section: Obrazovanje Za Radiounclassified